Targeting social assistance: Dibao and institutional alienation in rural China - Li, M; Walker, R (Wiley, 2016)
China’s Dibao (Minimal Living Security System) is the world’s biggest cash social assistance system serving 52 million people. However, Dibao is less effective at alleviating poverty in rural areas than should it be. The analytic concepts of targeting and institutional alienation (the mismatch between stated goals and true functioning) are applied in a village case-study to understand why. It appears that Dibao reaches some people considered self-evidently to be needy but funds are diverted for purposes of rural governance and social control (reward, punishment and deterrence) and personal gain. Though culturally framed, the concepts and findings potentially have relevance to the global South and North.